Devices of Lie Detection as Diegetic Technologies in the "War on Terror". (June 2015) - Egbert, Simon; Paul, Bettina
Although lie detection procedures have been fundamentally criticized since their inception at the beginning of the 20th century, they are still in use around the world. In addition, they have created some remarkable appeal in the context of counterterrorism policies. Thereby, the links between science and fiction in this topic are quite tight and by no means arbitrary: In the progressive narrative of the lie detection devices, there is a promise of changing society for the better, which is entangled in a fictional narrative provided by many cinematic and literary examples. By drawing on the concept of "diegetic technologies" formulated by David Kirby, we want to highlight the role of science fictional narratives in the historical development and current application of lie detection procedures. We therefore aim to use this conceptual frame to analyze the role of prevention-oriented mind reading procedures, which are developed for or already used in the "war on terror" with reference to their fictional predecessors. One virulent factor has to be highlighted in this context: The fictional engagement with possible new lie detection practices is in itself creating a legitimating ground for future security technologies.